Switching between pitch surfaces: practical applications and future perspectives for soccer training - Rago, V.; Silva, J. R.; Brito, J.; Barreira, D.; Mohr, M.; Krustrup, P.; Rebelo, A. N. (The Journal of Sports Medicine and Physical Fitness, 2019)
INTRODUCTION: Soccer training and completion is conventionally practiced on natural grass (NG) or artificial turf (AT). Recently, AT pitches for training/competition, and of unstable surfaces for injury prevention training has increased. Therefore, soccer players are frequently exposed to variations in pitch surface during either training or competition. These ground changes may impact physical and physiological responses, adaptations as well as the injury. The aim of this review was to summarize the acute physical and physiological responses, chronic adaptations, and injury risk associated with exercising on different pitch surfaces in soccer. EVIDENCE ACQUISITION: Eligible studies were published in English, had pitch surface as an independent variable, and had physical, physiological or epidemiological information as outcome variables. Specific data extracted from the articles included the training response, training adaptations or injury outcomes according to different pitch surfaces. A total of 224 studies were retrieved from a literature search. EVIDENCE SYNTHESIS: Twenty articles met the inclusion criteria: 9 for acute physical and physiological responses, 2 for training adaptations and 9 for injury assessment. The literature lacks consistent evidence regarding the effects of pitch surface on performance and health outcomes in soccer players. However, it seems that occasionally switching training surfaces seems a valuable strategy for focusing on specific musculoskeletal queries and enhancing players` fitness. For instance, sand training may be occasionally proposed as complementary training strategy, given the recruitment of additional musculature probably not involved on firmer surfaces, but the possible training-induced adaptations of non-conventional soccer surfaces (e.g., sand) might potentially result into a negative transfer on AT or NG. CONCLUSIONS: Since the specific physical demands of soccer can differ between surfaces, coaches should resort to the use of non-traditional surfaces with parsimony, emphasizing the specific surface-related motor tasks, normally observed on natural grass or artificial turf. Further studies are required to better understand the physiological effects induced by systematic surface-specific training, or switching between pitch surfaces.